Environmental law and economics : theory and practice / Michael G. Faure, Roy A. Partain. - Faure, Michael (Michael G.); Partain, Roy (Cambridge University Press, 2019)
In Environmental Law and Economics, Michael G. Faure and Roy A. Partain provide a detailed overview of the law-and-economics methodology developed and employed by environmental lawyers and policymakers. The authors demonstrate how this approach can transcend political divisions in the context of international environmental law, environmental criminal law, and the property rights approach to environmental law. Private law solutions and public regulatory approaches are also explored, including traditional command-and-control and market-based forms of regulation. The book not only shows how the law-and-economics framework can be used to protect the environment, but also to examine deeper questions involving environmental federalism and the effectiveness of environmental law in developing economies. In clear, digestible prose that does not require readers to possess a background in microeconomics or mathematics, the authors introduce the theory and practice of environmental law and economics that have been so critical in the creation of robust environmental policy.